Innovation - Agarwal, Renu (Professor of Operations and Supply Chain Management); Patterson, Eric (Director for a multinational consulting firm); Pugalia, Sancheeta; Green, Roy, 1951- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"In recent years, a great deal of attention has focused on the undertaking of managing innovation. Without the right focus, resourcing and capabilities, firms struggle to create value through innovation. However, the task of managing innovation is one of continuous paradoxes where an overly structured mind-set can impede entrepreneurship, creativity, culture and the right conditions for disruption. The question remains of how we can have the right lens to properly understand and appreciate innovation, and how we can have a flexible set of tools, techniques and perspectives to support innovation. This concise text introduces readers to one of the fundamental ideas in the business world. Insights into the key ingredients of innovation, including business models, services, entrepreneurship, and creativity are analysed alongside core contexts, such as disruptive technology. Students of business and management will appreciate additional coverage of the future of the field, including open innovation and the dark side of digital disruption. This accessible book provides a thought-provoking, stimulating perspective that will make it a valuable resource for a range of academic and student audiences across business and management disciplines"--
Keywords: Business enterprises -- Technological innovations; Information technology -- Management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management